Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Hyperbaric oxygen therapy attenuates carbon monoxide-induced lung injury by restoring mitochondrial dynamics and suppressing Pink1/Parkin-mediated mitophagy - Tzu-Hao Chen; Chien-Chin Hsu; Ching-Ping Chang; Chien-Cheng Huang; Ying-Jan Wang (Environmental Pollution, 2025)

Exploring community energy cum Aquavoltaics in Taiwan - Sin Yee Tan; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Aquaculture, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Testing the moderated mediation effect of recreation safety climate on the interrelationship of serious leisure, recreation involvement, and flow experience - Tien-Ming Cheng; Ching-Yi Hsu; Shan-Ni Li (Journal of Outdoor Recreation and Tourism, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Property rights arrangement and stakeholder networks hindering floating photovoltaics: A case of private open-access ponds in Taiwan - Yi-Chieh Chen; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Energy Policy, 2024)

Generation of artificial rainfall events for flood risk assessment in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Wei-Ling Chiang; Dung-Jiang Chiou; Cheng-Wu Chen (Natural Hazards, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Post-administration labeling with Palladium(II) ions enables ICP-MS-based determination of the biodistribution of carbonized nanogels - Hsu-Liang Huang; Chih-Ching Huang; Cheng-Kuan Su (Analytica Chimica Acta, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Caffeine ingestion improves power output decrement during 3-min all-out exercise - Ching-Feng Cheng; Wei-Chieh Hsu; Yu-Hsuan Kuo; Ming-Tsung Shih; Chia-Lun Lee (European Journal of Applied Physiology, 2016)

Voltage-Current-Adjusted Low-power Video Decoder Chip Design with Validation for Wireless Panoramic Endoscope - Ching-Hwa Cheng; Sheng-Wei Hsu (Journal of Medical and Biological Engineering, 2016)

Cocaine Withdrawal Impairs mGluR5-Dependent Long-Term Depression in Nucleus Accumbens Shell Neurons of Both Direct and Indirect Pathways - Chiung-Chun Huang; Ying-Ching Liang; Cheng-Che Lee; Kuei-Sen Hsu (Molecular Neurobiology, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Expression and Biologic Significance of Adiponectin Receptors in Papillary Thyroid Carcinoma - Shih-Ping Cheng; Chien-Liang Liu; Yi-Chiung Hsu; Yuan-Ching Chang; Shih-Yuan Huang; Jie-Jen Lee (Cell Biochemistry and Biophysics, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Isolation and Identification of a Novel Antioxidant with Antitumour Activity from Serratia ureilytica Using Squid Pen as Fermentation Substrate - Yao-Haur Kuo; Tzu-Wen Liang; Kao-Cheng Liu; Ya-Wen Hsu; Hsiu-Ching Hsu; San-Lang Wang (Marine Biotechnology, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Differential distributions of CSE1L/CAS and E-cadherin in the polarized and non-polarized epithelial glands of neoplastic colorectal epithelium - Wu-Ching Uen; Cheng-Jeng Tai; Shing-Chuan Shen; Woan-Ruoh Lee; Tang-Yi Tsao; Win-Ping Deng; Hung-Yi Chiou; Chung-Huei Hsu; Cheng-I Hsieh; Ching-Fong Liao; Ming-Chung Jiang (Journal of Molecular Histology, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Complex genomic organization of Indian muntjac centromeric DNA - Ya-Ming Cheng; Tzai-Shiuan Li; Lie-Jiau Hsieh; Pei-Ching Hsu; Yueh-Chun Li; Chyi-Chyang Lin (Chromosome Research, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

Effect of metal binding and posttranslational lysine carboxylation on the activity of recombinant hydantoinase - Cheng-Yang Huang; Ching-Chen Hsu; Mei-Chun Chen; Yuh-Shyong Yang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Meteorologically Adjusted Ground Level Ozone Trends in Southern Taiwan - Kuang-jung Cheng; Che-hui Tsai; Hsu-cherng Chiang; Ching-wen Hsu (Environmental Monitoring and Assessment, 2007)